Птицы - Бабенко Владимир Григорьевич (Детская энциклопедия РОСМЭН, 2014)
Экземпляры: Ф18 (20160218) / Инвентарный номер: 51603 / Цена: 110.00 / Сис.шифр: 28.693.35я2ср / Авт.знак: Б 12 / ГРНТИ: 34 / ББК: 28.693.35я2ср